The theatre of the coryphaei in Georgia: types and forms of ukrainian-georgian literary relations in the nineteenth century - ГРИЦИК, Людмила (Видавничо-поліграфічний центр “Київський університет”, 2025)
The article aims to interpret the activity of the Theatre of the Coryphaei in Georgia from a literary studies perspective, rather than a traditional theatre studies approach. It aims to assess the role of this theatre in the development of Ukrainian- Georgian literary and artistic relations and in the formation of new, previously unaccented types and forms of interliterary interaction, such as Ukrainian-language performances and non-translated works, which contributed to the reception of the Ukrainian word. The study is grounded in Ukrainian-Georgian relations of earlier periods, including personal contacts, translations, especially Taras Shevchenko's Testament, and historical events, for example the life and creative work of D. Guramishvili, the activities of M. Hulak, particularly his interpretation of Shota Rustaveli's The Knight in the Panther's Skin, as well as the work of O. Navrotskyi. During the period of the Theatre of the Coryphaei in Georgia, special attention is paid to D. Mordovets, whose novel The Descendants of Prometheus was widely known among the Georgian intelligentsia, and to T. Sakhokia, a prominent public figure, linguist, and literary scholar who maintained close contacts with Ukraine, among others. As the analysis of the material demonstrates, education, particularly at the Kyiv Theological Seminary, as well as the presence of representatives of the Georgian intelligentsia in Ukraine for various purposes, including K. Kekelidze, P. Melikishvili, and D. Uznadze, later renowned scholars and cultural figures, played a significant role in the specific reception of the Theatre of the Coryphaei's performances, which were staged in the original language. Performances of the Theatre of the Coryphaei in Georgia testified that, despite numerous prohibitions, the Ukrainian word continued to live and develop. Almost all members of the theatre were also engaged in literary activity. An important factor in shaping the specific features of the reception of Ukrainian- language works was the fact that, to renew and expand the theatre's repertoire, actors, including M. Starytskyi, not only wrote their own plays but also adapted works by Ukrainian and foreign authors, such as E. Franzos, E. Orzeszkowa, Yu. Kraszewski, and M. Gogol. As a result, what emerged was an encounter with one's own translated material through the prism of another, foreign-language work, most often reworked individually. These practices proved more powerful than any attempts to prohibit the Ukrainian word and to discredit the very existence of Ukrainian theatre. Our task is to demonstrate the role and functions of new types and forms of interliterary and artistic relations in the reception of Ukrainian literature.

У статті зроблено спробу з погляду не традиційно театрознавчого, а літературознавчого осмислити діяльність театру корифеїв у Грузії, оцінити роль його (театру) в розвитку українсько- грузинських літературно-мистецьких взаємин, виробленні нових, не проакцентованих видів і форм міжлітературних взаємин (наприклад, україномовних вистав, не перекладених творів), що сприяли рецепції українського слова. На ґрунті українсько-грузинських взаємин попередніх періодів (особистих контактів, перекладів, особливо "Заповіту" Т. Шевченка), історичних подій, наприклад, життя і творчості Д. Гурамішвілі, діяльності М. Гулака, особливо його прочитання "Витязя в тигровій шкурі" Ш. Руставелі, О. Навроцького, а в часи театру корифеїв у Грузії - Д. МорДовця, роман якого "НащаДки Прометея" був на слуху грузинської інтелігенції, Т. Сахокії - відомого громадського діяча, мовознавця і літературознавця, який піДтримував контакти з Україною тощо. Як показує робота з матеріалом, неабияке значення в особливій рецепції вистав театру корифеїв (вони йшли мовою оригіналу) мало також навчання (особливо в Київській Духовній семінарії), або ж з різною метою перебування преДставників грузинської інтелігенції в Україні (К. КекеліДзе, П. Мелікішвілі, Д. УзнаДзе та ін., згоДом віДомих учених, Діячів культури). Вистави театру корифеїв у Грузії засвіДчували: попри численні заборони українське слово живе і розвивається. ЛеДь не всі учасники театру також працювали і в літературі. Неабияку роль в особливостях рецепції україномовних творів мало й те, що з метою оновлення і розширення репертуару театру актори, наприклаД М. Старицький, не лише писали свої п'єси, але й переробляли твори вітчизняних та зарубіжних авторів (Е. Францоза, Е. Ожешко, Ю. Крашевського, М. Гоголя та ін.). Таким чином спостерігалося своє, перекладене, крізь призму чужого, іномовного твору, найчастіше перероблене на свій лад. Ці кроки були сильнішими проти будь-яких намагань заборонити українське слово і дискредитувати саме існування українського театру. Нашим завданням, отже, є показати роль, функції нових видів і форм міжлітературних мистецьких взаємин у рецепції української літератури.
Театр корифеїв у Грузії: до питання видів і форм українсько-грузинських літературних взаємин ХІХ століття
Keywords: Ukrainian-Georgian literary and artistic relations; types and forms; the Theatre of the Coryphaei; reception; українсько-грузинські літературно-мистецькі взаємини; види і форми; театр корифеїв; рецепція